2021
DOI: 10.1016/j.eclinm.2021.100804
|View full text |Cite
|
Sign up to set email alerts
|

Interval breast cancer rates for digital breast tomosynthesis versus digital mammography population screening: An individual participant data meta-analysis

Abstract: Background: Digital breast tomosynthesis (DBT) improves breast cancer (BC) detection compared to mammography, however, it is unknown whether this reduces interval cancer rate (ICR) at follow-up. Methods: Using individual participant data (IPD) from DBT screening studies (identified via periodic literature searches July 2016 to November 2019) we performed an IPD meta-analysis. We estimated ICR for DBTscreened participants and the difference in pooled ICR for DBT and mammography-only screening, and compared inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
2
11
1
Order By: Relevance
“…These results are in line with results from prospective studies, as for CD at baseline, 5,9,28 interval cancer 5,28 and subsequent screening 16,17 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are in line with results from prospective studies, as for CD at baseline, 5,9,28 interval cancer 5,28 and subsequent screening 16,17 …”
Section: Discussionsupporting
confidence: 89%
“…These results are in line with results from prospective studies, as for CD at baseline, 5,9,28 interval cancer 5,28 and subsequent screening. 16,17 This design allows to evaluate whether a net increase in CD of DBT vs DM exists in the screened population, overcoming the potential bias of the learning curve linked to successive DBT rounds, and to estimate the lead time gain of DBT vs DM.…”
Section: Lead Time Gainsupporting
confidence: 90%
“…However, even larger studies on aggregated data are necessary. Our study has been included in published meta-analyses on interval cancer, but even these meta-analyses proved to be insufficiently powered (166,167). Additional long-term studies on interval cancer rates in consecutive screening rounds may add knowledge.…”
Section: Screening With Dbtmentioning
confidence: 99%
“…Many studies have shown that the combination of DBT with FFDM enhances breast cancer detection while reducing the recall rate during screening [13][14][15]. For diagnostic purposes, DBT demonstrates a comparatively higher breast cancer detection rate than FFDM alone [16,17]. However, the DBT procedure combined with a 2D-digital mammographic (2D-DM) image doubles the radiation dose, although it provides more accurate details than a DM image alone [10].…”
Section: Introductionmentioning
confidence: 99%